Integration Of Labor Law In Islamic Law And Civil Law Citizenship (Harmonization Of Principles And Their Implementation In Contemporary Society) - Weny Almoravid Dungga; Awad Al-Khalaf (LPPM Universitas Trunojoyo Madura, 2022)
Integrating labor law into Islamic and civil law is a process to harmonize principles and implementation in contemporary society. Does this study aim to answer (1) How can labor law principles in Islamic law be integrated with civil law for citizenship to create harmonization in its implementation? Moreover, (2) What challenges and obstacles are faced in integrating Labor Law into Islamic Law and Citizenship Civil Law in contemporary society? This study's research type is the normative juridical method, whose other name is doctrinal legal research, also known as library research or document study. The research results show that to integrate the principles of labor law in Islamic law with civil law on citizenship, several strategic steps need to be taken—first, open dialogue and discussion between Islamic law experts and civil law on citizenship. Second, they draft laws and regulations that accommodate the principles and norms of both legal systems. Third, involving inclusive and interdisciplinary legal education and fourth, educating the public about the benefits and objectives of integrating labor law into Islamic and civil law on citizenship. Fifth, increase cooperation between countries and international organizations.